Interpretation of the Hadith Regarding the Command to Wipe the Khuf: Study of AGH. Lanre Said’ Work in the Islamic Law Perspective - Tangngareng, Tasmin; Wangsa, Fadhlina Arief; Rayyn, I Gusti Bagus Agung Perdana (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
One aspect that is very important to pay attention to is related to purification in the realm of worship, including the command to wipe the khuf. Wiping the khuf is the ability to wipe one's shoes as a form of relief and as a substitute for wiping one's feet when performing ablution. However, this is still very rarely known by Muslims. This article aims to elaborate on the hadith regarding the command to wipe the khuf contained in the book al-Żikrā by AGH. Lanre Said. This is a descriptive qualitative research using the ma'ānī al-ḥadīṣ science approach, which is a contextual interpretation technique in analyzing the Islamic law contained in the hadith. The data is then analyzed and elaborated using contextual interpretation techniques. The results of the research show that contextually khuf is anything that is used to cover the feet made of thick cloth or leather. According to the science of ma‘ānī al-ḥadīṣ, considering asbāb al-wurud and paying attention to social situations and realities, this hadith must be understood contextually. Interpretation and understanding of the hadith contained in his work uses contextual understanding, in accordance with current developments. As for the Islamic law, the order to wipe the khuf only applies temporally or conditionally, even in the current context the order to wipe the khuf is only optional. The command to wipe the khuf according to Islamic law is basically permissible. Understanding this hadith will have implications for the elastic and flexible application of the Islamic law in the society.